2013
DOI: 10.12816/0003312
|View full text |Cite
|
Sign up to set email alerts
|

Discharge against Medical Advice among Children in Oman : A University Hospital Experience = الخروج ضد المشورة الطبية بين الأطفال في عمان : تجربة مستشفى جامعي

Abstract: abstract:Objectives: Discharge against medical advice (DAMA) is a major problem in healthcare delivery as it can complicate the health problems from which patients are suffering. The aim of this study was to understand DAMA among children in a tertiary teaching hospital in Oman and to evaluate the documentation of the events in the medical records. Methods: A retrospective survey of the medical records of patients discharged against medical advice over a two-year interval was performed (2004)(2005)(2006). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
1
17
1
Order By: Relevance
“…This is because health care is free for patients in Oman, while in other countries where health care is not free, financial factors might contribute to DAMA. Also, the other reasons associated with dissatisfaction with hospital services did not play a big role in DAMA, in contrast with other studies (Al Saadoon and Al Shamousi 2013), which could be a real satisfaction or reporting bias as the method of data collection could affect the mothersresponses.…”
Section: Reasons and Factors Associated With Damacontrasting
confidence: 76%
See 3 more Smart Citations
“…This is because health care is free for patients in Oman, while in other countries where health care is not free, financial factors might contribute to DAMA. Also, the other reasons associated with dissatisfaction with hospital services did not play a big role in DAMA, in contrast with other studies (Al Saadoon and Al Shamousi 2013), which could be a real satisfaction or reporting bias as the method of data collection could affect the mothersresponses.…”
Section: Reasons and Factors Associated With Damacontrasting
confidence: 76%
“…This study found a small percentage of families seeking traditional care for the children (6.4%), compared with other studies (Al Saadoon and Al Shamousi 2013). This is very important as there are many risks expected from such practices and might expose child life to risk (delay in starting proper treatment, exacerbate pre-existing health problems, risk from the traditional treatment).…”
Section: Reasons and Factors Associated With Damamentioning
confidence: 47%
See 2 more Smart Citations
“…1,11 In contrast, Al-Sadoon et al and Abdulateef et al reported a LAMA prevalence of only 0.32% and 0.11% in Oman and Qatar, respectively. 12,13 The setting of the latter study was different from other studies as it was conducted in a paediatric emergency centre within the ideal observation period of 48 hours. 13 Al-Turkistani reported a LAMA prevalence of 1.6% in a neonatal intensive care unit at a university hospital in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%